Presplitting Blasting the Roof Strata to Control Large Deformation in the Deep Mine Roadway - Chaowen Hu; Xiaojie Yang; Ruifeng Huang; Xingen Ma (Advances in Civil Engineering)
As the mining depth increases, under the influence of high ground stress, the surrounding rock of deep mine roadways shows soft rock characteristics. Under the influence of mining disturbance at the working face, large deformation of the roadway has occurred. To control the large deformation of the roadway, many mines have adopted the form of combined support, which has continuously increased the support strength and achieved a certain effect. However, since the stress environment of the surrounding rock of the roadway has not been changed, large deformation of the roadway still occurs in many cases. Based on the theoretical basis of academician Manchao He’s “short cantilever beam by roof cutting,” this paper puts forward the plan of “presplitting blasting + combined support” to control the large deformation of the deep mine roadways. Without changing the original support conditions of the roadway, presplitting blasting the roof strata of the roadway, by cutting off the mechanical connection of the roof strata between the roadway and gob, improves the stress distribution of the roadway to control the large deformation. Through field tests, the results show that after presplitting blasting the roadway roof, the roadway roof subsidence is reduced by 47.9%, the ribs displacement is reduced by 45.7%, and the floor heave volume is reduced by 50.8%. The effect is significant.